IMPLEMENTASI MANAJEMEN PENDIDIKAN ISLAM DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI ERA DIGITAL - Toni Wijaya; Nurul Hidayati Murtafiah (Najah Bestari, 2023)
Implementation of Islamic Education Management (MPI) in improving the quality of learning in the digital era is becoming increasingly important in optimizing the use of technology in the learning process and ensuring that good Islamic values ​​are taught and implemented in students' daily lives. Islamic Education Management (MPI) can help ensure that learning is not only effective and relevant, but also takes into account the needs of students in an increasingly complex and diverse digital era. In addition, Islamic Education Management (MPI) can also help minimize risks and create a safe and effective learning environment. The research method used in this study is a qualitative descriptive method with a literature study approach. This research was conducted by collecting data from various sources related to the implementation of Islamic Education Management in improving the quality of learning in the digital era. In the Implementation of Islamic Education Management, several steps need to be taken, including making strategic plans, having an effective management system, applying appropriate educational technology, making curricula relevant and according to needs, providing adequate resources, implementing interactive and creative learning. , as well as measuring and evaluating performance. By implementing Islamic Education Management (MPI) in improving the quality of learning in the digital era, it is expected to create learning that is effective, relevant, and in accordance with the needs of students and society in the digital era.